Pengaruh Pendapatan Asli Daerah (PAD), Dana Bagi Hasil (DBH), Dana Alokasi Umum (DAU), Dana Alokasi Khusus (DAK) Terhadap Belanja Daerah (BD) Dan Fenomena Flypaper Effect Kabupaten/Kota Di Provinsi Kalimantan Selatan - Muhammad Yasir; Muhammad Saleh (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
The aim of research are (1) to know effect partially and simultaneously original local revenues (PAD), revenue sharing funds (DBH), general allocation funds (DAU), special allocation funds (DAK) to regional expenditures (BD) regency/city in South Kalimantan Province, (2) to know occurence flypaper effect phenomenon regency/city in South Kalimantan Province. The object of research are 13 auotonomous region in South Kalimantan Province (11 regencies and 2 cities). The data of research from DJPK Kemenkeu RI and Bakeuda of South Kalimantan Province. Technical analysis used panel data regression and detection flypaper effect with compare coefficient of PAD to DBH, DAU, DAK. The result of research showed by partially and simultaneusly PAD, DBH, DAU, DAK have significant effect to BD regency/city in South Kalimantan Province on 2004-2017 and no occurance flypaper effect because coefficient regression of PAD is greater than coefficent regression of DBH, DAU, DAK.